2015
DOI: 10.2337/dc15-1042
|View full text |Cite
|
Sign up to set email alerts
|

Arterial Wall Elastic Properties and Endothelial Dysfunction in the Diabetic Foot Syndrome in Patients With Type 2 Diabetes

Abstract: Diabetic foot (DF) syndrome is the most common lower-extremity complication of poorly controlled type 2 diabetes (T2D) (1). DF affects the quality of life of T2D patients and is associated with increased morbidity (2). T2D-related mechanisms induce endothelial dysfunction and adverse effects on vascular biology (3). We have recently shown that measurements of endothelial function and arterial stiffness are strongly associated with diabetic retinopathy (4), but their association with DF has not been explored ye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 4 publications
1
8
0
Order By: Relevance
“…In another study Antonopoulos et al reported [28] that both brachial FMD and AIx are strongly and independently associated with DFS.…”
Section: Discussionmentioning
confidence: 99%
“…In another study Antonopoulos et al reported [28] that both brachial FMD and AIx are strongly and independently associated with DFS.…”
Section: Discussionmentioning
confidence: 99%
“…Vascular dysfunction is one of the initial steps in the atherosclerotic process [17, 18]. Endothelial function and arterial stiffness [17, 19] are two widely used indices of vascular function, which both offer prognostic information on the risk of CVD events in T2D patients [19]. Improvement of these indices represents one of the mechanisms by which drugs with established CVD benefits, such as statins, exert their effects [20, 21].…”
Section: Introductionmentioning
confidence: 99%
“…The systematic search resulted in the inclusion of 193 from a total of 4641 potential articles (Figure ). From the 193 studies included in the analyses, vascular reactivity was assessed in a total of 26570 patients that were considered healthy (n = 7226), overweight (n = 7605), or those with obesity (n = 1758) or that were diagnosed with metabolic sy...…”
Section: Resultsmentioning
confidence: 99%